Assessing the Evidence in Indigenous Education Research Implications for Policy and Practice - Moodie, Nikki; Lowe, Kevin; Dixon, Roselyn; Trimmer, Karen (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores the current state of research on Indigenous education Australia. In particular, these chapters focus on exploring deep and enduring questions about the failures of schooling to address the needs of Aboriginal communities. This book provides a systematic analysis of existing research to explain how connection to culture - and the recognition of Indigenous sovereignties and knowledges - are the keys to Aboriginal excellence in schooling.
The Aboriginal Voices Project: What matters, and who counts, in Indigenous education -- Developing a systematic methodology to explore research in Indigenous education -- The benefit of Indigenous cultural programs in schools -- Understanding the evidence on racism & Indigenous schooling -- Improving school engagement with Indigenous communities -- Professional learning and teacher identity in Indigenous education -- Knowing in Being: An understanding of Indigenous knowledge in its relationship to reality through enacted curriculum -- Innovative school leadership: Impacting Aboriginal student outcomes into the future -- What does quality teaching look like for Indigenous Australian students and how do we know? -- Interrogating Indigenous student literacy programs -- What next? Building on the evidence of teaching and learning mathematics for Aboriginal and Torres Strait Islander students -- Making a difference in educational outcomes for remote First Nations students -- What's the problem represented to be? Analysing Indigenous education policy as discourse -- The foundations required for First Nations education in Australia. .
Keywords: Education -- Research; Educational sociology; Ethics; Research Methods in Education; Sociology of Education; Moral Philosophy and Applied Ethics; Sociology of Education